Can Serum ST2 Levels Be Used as a Marker of Fibrosis in Chronic Hepatitis B Infection?. Issue 47 (November 2015) - Oztas, Erkin; Kuzu, Ufuk Baris; Zengin, Neslihan Inci; Kalkan, Ismail Hakki; Onder, Fatih Oguz; Yildiz, Hakan; Celik, Huseyin Tugrul; Akdogan, Meral; Kilic, Mesut Yalin; Koksal, Aydin Seref; Odemis, Bulent; Suna, Nuretdin; et al.
Abstract : Abstract: Interleukin 33 (IL-33) is a cytokine belonging to the IL-1 superfamily. Soluble ST2 (sST2) binds to IL-33 and by functioning as trap receptor inhibits signal sending to Th2 via transmembrane ST2. Because Th2-type cytokines play an important role in fibrosis, the aim of this study is to determine whether sST2 can be used as a marker of fibrosis in chronic hepatitis B (CHB) patients or not. The study included 19 healthy controls, 54 patients with CHB, and 14 patients with cirrhosis because of CHB. The aspartate aminotransferase-to-platelet ratio index (APRI) and fibrosis index based on the 4 factors (FIB-4) scores also calculated, and correlations between liver biopsies, sST2 levels, and these scores were analyzed in CHB and cirrhosis patients. The sST2 levels in patients with CHB were significantly higher than those in the control group subjects (median: 1133 pg/mL vs 762.5 pg/mL, respectively [ P  = 0.035]). In CHB patients, the METAVIR fibrosis score (stages from 0 to 4) showed a moderate correlation with serum sST2 level ( r  = 0.396, P  = 0.004) and a weak correlation with FIB-4 score ( r  = 0.359, P  = 0.008), but no correlation with APRI score ( r  = 0.253, P  = 0.06). The under the curve value of serum sST2 was 0.68, and its prediction of significant fibrosis (METAVIR score ≥2) in values >674 pg/mL had a sensitivity of 91.7% and specificity of 40% ( P  = 0.009). According to multiple logistic regression analysis, only METAVIR fibrosis stage was found to be an independent predictor of serum sST2 elevation in CHB patients ( P  = 0.04). The sST2 level can be used for differentiating significant fibrosis from mild fibrosis in CHB patients. However, the efficacy of this marker should be verified by larger studies in the future.